Use of aids for smoking cessation and alcohol reduction: A population survey of adults in England - Emma Beard; Jamie Brown; Susan Michie; Eileen Kaner; Petra Meier; Robert West (BMC, 2016)
Abstract Background It is important for policy planning to chart the methods smokers and high-risk drinkers use to help them change their behaviour. This study assessed prevalence of use, and characteristics of users, of support for smoking cessation and alcohol reduction in England. Methods Data were used from the Smoking and Alcohol Toolkit Studies, which involve monthly face-to-face computer-assisted interviews of adults aged 16+ in England. We included data collected between June 2014 and July 2015 on 1600 smokers who had made at least one quit attempt and 911 high-risk drinkers (defined as scores >8+ on the full AUDIT or 5+ on questions 1-3 of the AUDIT-C) who had made an attempt to cut down in the past 12 months. Participants provided information on their socio-demographic characteristics and use of aids during their most recent quit attempt including pharmacotherapy, face-to-face counselling, telephone support, self-help materials (digital and printed), and complementary medicine. Results A total of 60.3% of smokers used aids in the past year, compared with just 14.9% of high-risk drinkers. Use of pharmacotherapy was high among smokers and very low among drinkers (56.0%versus1.2%). Use of other aids was low for both behaviours: face-to-face counselling (2.6%versus4.8%), self-help materials (1.4%versus4.1%) and complementary medicine (1.0%versus0.5%). Use of aids was more common among smokers aged 25-54 compared with 16-24 year olds (25-34,ORadj1.49,p = 0.012; 35-44,ORadj1.93,p < 0.001; 35-44,ORadj1.93,p < 0.001; 45-54,ORadj1.66,p = 0.008), with cigarette consumption >10 relative to <1 (10-20,ORadj2.47,p = 0.011; >20,ORadj4.23,p = 0.001), and less common among ethnic minorities (ORadj0.69,p = 0.026). For alcohol reduction, use of aids was higher among ethnic minority groups (ORadj2.41;p = 0.015), and those of social-grade D/E relative to AB (ORadj2.29,p = 0.012&ORadj3.13,p < 0.001). Conclusion In England, the use of pharmacotherapy is prevalent for smoking cessation but not alcohol reduction. Other aids are used at a low rate, with face-to-face counselling being more common for alcohol reduction than smoking cessation.